The diagnosis of adult-onset haemophagocytic lymphohistiocytosis: lessons learned from a review of 29 cases of bone marrow haemophagocytosis in two large academic institutions. Issue 9 (19th February 2016) - Rosado, Flavia G; Rinker, Elizabeth B; Plummer, W D; Dupont, William D; Spradlin, Natalie M; Reichard, Kaaren K; Kim, Annette S
Abstract : Aims: Haemophagocytic lymphohistiocytosis (HLH) is divided into paediatric (primary) and adult (secondary) types. While paediatric-HLH has been extensively characterised, similar studies in adults are limited. This study aims to evaluate the significance of the HLH diagnostic criteria as well as other clinical parameters in adults with bone marrow evidence of haemophagocytosis. Methods: We conducted a 10-year retrospective search of the pathology archives of two institutions for cases with bone marrow haemophagocytosis. We included those cases that fulfilled the currently established HLH diagnostic criteria. For the 29 cases that met inclusion criteria, we assessed clinical features, co-morbidities, therapy and clinical outcome. The effect of 19 clinical variables on mortality outcomes was assessed using logistic and hazard regression analyses. Results: Of cases for which an aetiology could be identified, infectious diseases were the most common association (14 of 19, 74%). Fever and elevated ferritin were the most frequently available criteria used to establish HLH. The overall mortality rate was 61% despite HLH-specific therapy, which had been initiated in 48% of the cases. The remaining cases were treated with supportive therapy and antibiotics. The most statistically significant marker of mortality was an elevated absolute neutrophil count (ANC), a feature not typical of HLH. Conclusions: Since elevated ANC correlates with poor outcomes in sepsis, and not HLH, we postulate that many of the patients fulfilling HLH diagnostic criteria in this study likely had sepsis/systemic inflammatory response syndrome rather than HLH. Our results highlight the need to define HLH diagnostic criteria specific to the adult population.